Discrimination in the workforce: how it impacts a business - Whitfield, Deidre Raquel (2014)
Discrimination, in its best form, is a hard concept to fathom as an employee or ordinary citizen. In the workplace, there are times when discrimination is necessary due to extenuating circumstances that revolve around the form or act of discrimination. It could be conveyed to save a life or avoid future conflict. However, it must be clearly stated as a written law that the act is lawful. When unlawful discrimination occurs, it stages an entirely different tone, as it is mainly conducted out of malice, hatred, greed, control, or ignorance. Over the last few decades, discrimination has existed in the workplace, although Federal laws mandate that it does not occur. It does not exist in just one geographical area or is country specific, but covers a wide spectrum, linking countries together from their points of view to creating rifts amongst those who are affected and those who are not, not only from a business perspective, but social humanistic relationships as well. This thesis will use quantitative and qualitative data to support discrimination of sexual harassment, race or color, and gender issues, as well as personal experiences, and how it has and will continue to impact businesses if the acts do not cease, permanently. Leadership, from the Presidents and Heads of Countries, Chief Executive Officers (CEOs), managers, lowest-ranking supervisor, and employees should make it their personal goal to ensure these issues do not continue or arise in their perspective areas of responsibilities. When employees understand that they are valued, will be taken seriously when reporting acts of discrimination, and that some form of action will be taken, performance and productivity will escalate, and morale will increase in the workplace, resulting in higher productivity and subsequently higher profit margins for the company.